Ferroptosis and tumor immunotherapy: A promising combination therapy for tumors - Cai, Huazhong; Ren, Yongfei; Chen, Shuangwei; Wang, Yue; Chu, Liangmei (Frontiers in Oncology, 2023)
Low response rates and treatment resistance are frequent problems in the immunotherapy of tumors, resulting in the unsatisfactory therapeutic effects of some tumors. Ferroptosis is a form of cell death characterized by the accumulation of lipid peroxides. In recent years, it has been found that ferroptosis may be related to the treatment of cancer. Many cell types (such as macrophages, CD8+T cells) can cause ferroptosis in tumor cells through related pathways, and synergistically enhance the anti-tumor immune effects. But the mechanism is different for each type of cell. DAMP released in vitro by cancer cells undergoing ferroptosis can lead to the maturation of dendritic cells, cross-induction of CD8+T cells, IFN-γ production and M2 macrophages production. Thus, it activates the adaptability of the tumor microenvironment and forms the positive feedback of the immune response. This suggests that induction of ferroptosis may contribute to reduce resistance to cancer immunotherapy and has great potential in cancer therapy. Further research into the link between ferroptosis and tumor immunotherapy may offer hope for those cancers that are difficult to cure. In this review, we focus on the role of ferroptosis in tumor immunotherapy, explore the role of ferroptosis in various immune cells, and discuss potential applications of ferroptosis in tumor immunotherapy.